Is lactate an undervalued functional component of fermented food products? - Garrote, Graciela L.; Abraham, Analía G.; Rumbo, Martín (Frontiers in Microbiology, 2015)
Although it has been traditionally regarded as an intermediate of carbon metabolism and major component of fermented dairy products contributing to organoleptic and antimicrobial properties of food, there is evidence gathered in recent years that lactate has bioactive properties that may be responsible of broader properties of functional foods. Lactate can regulate critical functions of several key players of the immune system such as macrophages and dendritic cells, being able to modulate inflammatory activation of epithelial cells as well. Intraluminal levels of lactate derived from fermentative metabolism of lactobacilli have been shown to modulate inflammatory environment in intestinal mucosa. The molecular mechanisms responsible to these functions, including histone deacetylase dependent-modulation of gene expression and signalling through G-protein coupled receptors have started to be described. Since lactate is a major fermentation product of several bacterial families with probiotic properties, we here propose that it may contribute to some of the properties attributed to these microorganisms and in a larger view, to the properties of food products fermented by lactic acid bacteria.